The legal status of women on marriage and divorce under the civil law / Nor Azni Abas - Abas, Nor Azni (Faculty of Law, 1985)
History has shown that woman obtains no rights on marriage.She has no legal rights and in fact she was once considered as a chattel of her husband. A wife could not even own a property of her own, everything that belongs to her, on marriage passes to her husband. Formerly a husband was entitled to compel his wife to carry out her duty to live with him. This duty could be carried out by force if required and the wife could be sent to prison for failing to obey a court order that she should return. Nowdays this does not apply, rot if a wife leaves her husband she runs the risk of losing her right to financial support. She cannot, however, be forced to return to him. In the case of R V JackSon Mrs. Jackson was dragged from her carriage by Mr. Jacksou and an accomplice and imprisoned in her husbands house. A relative sucessfully applied for the writ of habeas corpus to release her and so finally